Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Kenalan Kopi, Tebing Tinggi - Kumala Vera Dewi; Muhammad Aziz Khiar (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2025)
This study aims to determine whether job satisfaction can mediate the influence of motivation on performance. The population of this study was 30 employees of Kenalan Kopi Tebing Tinggi. The sampling technique used was saturated sampling, because the population was less than 100 people. Questionnaires were administered to 30 respondents via Google Form. The research method used was a quantitative method with the assistance of SEM-PLS. The test results showed that motivation had an effect on job satisfaction, motivation had an effect on performance, job satisfaction had no effect on performance, and job satisfaction was unable to mediate the effect of motivation on performance.